ELF/VLF wave propagation at subauroral latitudes: Conjugate observation between the ground and Van Allen Probes A. Issue 6 (28th June 2016) - Martinez‐Calderon, Claudia; Shiokawa, Kazuo; Miyoshi, Yoshizumi; Keika, Kunihiro; Ozaki, Mitsunori; Schofield, Ian; Connors, Martin; Kletzing, Craig; Hanzelka, Miroslav; Santolik, Ondrej; Kurth, William S.
Abstract: We report simultaneous observation of ELF/VLF emissions, showing similar spectral and frequency features, between a VLF receiver at Athabasca (ATH), Canada, ( L = 4.3) and Van Allen Probes A (Radiation Belt Storm Probes (RBSP) A). Using a statistical database from 1 November 2012 to 31 October 2013, we compared a total of 347 emissions observed on the ground with observations made by RBSP in the magnetosphere. On 25 February 2013, from 12:46 to 13:39 UT in the dawn sector (04–06 magnetic local time (MLT)), we observed a quasiperiodic (QP) emission centered at 4 kHz, and an accompanying short pulse lasting less than a second at 4.8 kHz in the dawn sector (04–06 MLT). RBSP A wave data showed both emissions as right‐hand polarized with their Poynting vector earthward to the Northern Hemisphere. Using cross‐correlation analysis, we did, for the first time, time delay analysis of a conjugate ELF/VLF event between ground and space, finding +2 to +4 s (ATH first) for the QP and −3 s (RBSP A first) for the pulse. Using backward tracing from ATH to the geomagnetic equator and forward tracing from the equator to RBSP A, based on plasmaspheric density observed by the spacecraft, we validate a possible propagation path for the QP emission which is consistent with the observed time delay. Key Points: Conjugate observation of QP emission and accompanying short pulse between satellite and ground Time delay analysis shows QP observed first at ATH while short pulse observed first by RBSP A We successfully reproduced propagation of QP using in situ cold plasma density profile by RBSP A